Ciliogenesis associated kinase 1: targets and functions in various organ systems. Issue 21 (20th September 2019) - Fu, Zheng; Gailey, Casey D.; Wang, Eric J.; Brautigan, David L.
Abstract : Ciliogenesis associated kinase 1 (CILK1) was previously known as intestinal cell kinase because it was cloned from that origin. However, CILK1 is now recognized as a widely expressed and highly conserved serine/threonine protein kinase. Mutations in the human CILK1 gene have been associated with ciliopathies, a group of human genetic disorders with defects in the primary cilium. In mice, both Cilk1 knock‐out and Cilk1 knock‐in mutations have recapitulated human ciliopathies. Thus, CILK1 has a fundamental role in the function of the cilium. Several candidate substrates have been proposed for CILK1 and the challenge is to relate these to the mutant phenotypes. In this review, we summarize what is known about CILK1 functions and targets, and discuss gaps in current knowledge that motivate further experimentation to fully understand the role of CILK1 in organ development in humans. Abstract :